Comparison of approaches to nominal and relative clauses - Reitrová, Lucie (Univerzita Pardubice, 2008)
The work examines different approaches to the categorization of nominal and relative clauses. The classification of these clauses is introduced in the theoretical part. This classification is applied in the practical part, which compares frequency of occurrence of nominal and relative clauses in the European Union annual report.
Srovnání přístup k nominálním a vztažným větám
Keywords: větná skladba; vedlejší věta; nominální věta; obsahová věta; vztažná věta; vztažná věta substantivní; sentence structure; subordinate clause; nominal clause; content clause; relative clause; nominal relative clause